2021
DOI: 10.3389/fcell.2021.764725
|View full text |Cite
|
Sign up to set email alerts
|

CRISPR Generated SIX6 and POU4F2 Reporters Allow Identification of Brain and Optic Transcriptional Differences in Human PSC-Derived Organoids

Abstract: Human pluripotent stem cells (PSCs) represent a powerful tool to investigate human eye development and disease. When grown in 3D, they can self-assemble into laminar organized retinas; however, variation in the size, shape and composition of individual organoids exists. Neither the microenvironment nor the timing of critical growth factors driving retinogenesis are fully understood. To explore early retinal development, we developed a SIX6-GFP reporter that enabled the systematic optimization of conditions tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
32
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3
2

Relationship

3
7

Authors

Journals

citations
Cited by 24 publications
(32 citation statements)
references
References 108 publications
(136 reference statements)
0
32
0
Order By: Relevance
“… (A) Schematic overview summarizing hESC differentiation into retinal organoids using a 3D-2D-3D technique adopted from the Meyer and Zack labs. 26,27 (B) Representative images of important stages in RGC differentiation starting from hESCs to form embryoid bodies and optic vesicle-like structures in 3D culture before being moved to 2D culture to enable epithelial cell formation and then back to 3D culture to mature and generate RGCs (tdTomato positive cells). (C) Schematic of cell recruitment transwell assay and (D) representative immunofluorescent 3D reconstruction and en-face images of hRGCs on the apical and/or basal membrane surface following chemokine treatment.…”
Section: Resultsmentioning
confidence: 99%
“… (A) Schematic overview summarizing hESC differentiation into retinal organoids using a 3D-2D-3D technique adopted from the Meyer and Zack labs. 26,27 (B) Representative images of important stages in RGC differentiation starting from hESCs to form embryoid bodies and optic vesicle-like structures in 3D culture before being moved to 2D culture to enable epithelial cell formation and then back to 3D culture to mature and generate RGCs (tdTomato positive cells). (C) Schematic of cell recruitment transwell assay and (D) representative immunofluorescent 3D reconstruction and en-face images of hRGCs on the apical and/or basal membrane surface following chemokine treatment.…”
Section: Resultsmentioning
confidence: 99%
“…The other QC tests also had strong points. Recent study using RNA-seq approach revealed that Six6-negative off-target cells in retinal differentiation culture using Matrigel method contain multiple neural cells including Emx2-positive cells and HoxB2-positive cells (Wahlin et al, 2021). In addition, single cell analyses such as sc-RNA-seq are powerful technologies, and several groups have reported pioneered studies (Capowski et al, 2019; Collin et al, 2019; Cowan et al, 2020; Phillips et al, 2018; Sridhar et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…The migratory astrocytes and BSL cells from transplanted organoids display molecular profiles distinct from cells in mature cultured organoids. The astrocytes express PAX2 , which normally delineates the optic stalk in vivo 66 . PAX2 is detected in retinal progenitors in early-stage retinal organoids but is undetectable at later stages 65, 67 .…”
Section: Discussionmentioning
confidence: 99%